Geospatial assessment of the discharge of karst springs in the Zagros zone, Iran - Masoumeh Zare; Zargham Mohammadi; Ezzat Raeisi; Zoran Stevanovic; Rouhollah Adinehvand; Tao Peng (Journal of Hydrology: Regional Studies, 2024)
Study region: The area of exposed karstic carbonate formations in Zagros zone. Study focus: This study focused on geospatial variation of recorded discharge of 45842 karst springs, as a valuable indicators of karst development in carbonate terrains of Zagros zone (Asmari-Jahrum-Shahbazan, Ilam-Sarvak, and Fahlian-Darian) within eight major river basins (West Border, Karkheh, Karun, Jarahi-Zohreh, Heleh, Tashk-Bakhtegan-Maharlu, Mond, and Kol-Mehran). Results: The results show that while the number of low-discharge springs (<10 l/s) is largest, high-discharge springs (>500 l/s) significantly contribute to the annual discharge volume of karst aquifers. The Karun and Heleh river basins host the maximum (16,527) and minimum (633) number of springs, with annual discharge volumes of 4611 and 151 million m³, respectively. Notably, the Karun river basin contains 50 % of springs exceeding 500 l/s, contributing approximately 54 % to the total annual discharge (2528 million m³). The Asmari-Jahrum-Shahbazan karst system has the highest number of springs, accounting for 28.17 % of the total annual discharge volume. The Ilam-Sarvak system ranks second, surpassing the Fahliyan-Daryan system in annual discharge volume and development, despite both having an equal number of springs over 500 l/s. Asmari-Jahrum-Shahbazan formations show the least variability, while Ilam-Sarvak formations exhibit greater vulnerability to precipitation changes.